Etude de quelques aptitudes technologiques des bactéries lactiques du genre Lactobacillus - DERDACHI, Narimane; MAAZA, Manel (My University, 2021)
Lactic acid bacteria are naturally part of our environment and our food, they have acquired great importance through their presence in the food industry. In this study we selected 7 isolates of the genus Lactobacillus from raw cow milk in order to study their technological abilities. The milk sample was collected in the Sayada region (Mostaganem) and the isolates were purified and pre-identified by morphological, physiological and biochemical tests. The results of estimation of some technological abilities indicate that all the strains present a good acidifying and proteolytic activity. Strain 2N recorded the highest acidifying activity with 125°D. These strains have shown other abilities such as: texturizing, flavouring and lipolytic activity which can be exploited in the dairy industry. On the other hand, we tested the antagonistic activity of our isolates against three pathogenic bacteria Staphylococcus aureus, Bacillus cereus and Proteus vulgaris. According to the results we obtained, the Lactobacillus isolates inhibited two target bacteria with inhibition zones ranging from 4mm to 19mm. Thus, cow's milk can be considered as an ecosystem allowing the development of a lactic microflora with technological interest.
Keywords: Lactic bacteria, Lactobacillus, cow's milk, technological aptitude.